Business Model Analysis and Innovation of Jumputan Industry Using the Value Chain and It Balanced Scorecard Approach - Ainun Hilaliyyah; Muhammad Izman Herdiansyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Palembang Jumputan Fabric SMEs are an interesting industry to analyze using the E-Business chain application value and performance measurement using the concept IT Balanced Scorecard that can help Palembang jumputan fabric SMEs entrepreneurs control performance and provide feedback in developing its operational performance. The technique of analyzing the data uses a quantitative descriptive approach, which describes a data in the form of numbers obtained from enumeration and counting.  To achieve competitive advantage, companies must pay more attention to three aspects, namely, Service, Quality and Price. The highest value added was received by the jumputan craftsmen, which was 19.43%, with a value of Rp. 35,737, the second added value is on the shop side, which is 7.19% with a large value of Rp. 17,211. The use of information technology at Griya Kain Tuan Kentang has not been able to contribute to the organization, support user orientation, support operational activities, and has not been able to compete in the future. The final result in measuring the performance of information technology users at Griya Kain Tuan Kentang is 60.63%.